Review of Lithuanian experience in asphalt pavements cold recycling - Vaitkus, Audrius; Gražulytė, Judita; Juknevičiūtė-Žilinskienė, Lina; Andrejevas, Vitalijus (International Conference “Environmental Engineering”, 2017)
One of the key goals in the EU White Paper is to reduce carbon emissions in transport by 60% by 2050. Consequently, during the past years an effect on the environment became a decisive factor in selecting materials and technologies for road construction and rehabilitation. Cold recycling is a reasonable solution in asphalt pavement rehabilitation because it is economical and old asphalt pavements can be reused. This technology differs from others by mixing temperature. Besides, cold recycling does not require additional heating. These benefits result in wide application of cold recycling around the world. In Lithuania, cold recycling has been used for more than 15 years. Both technologies, i.e. cold in lant recycling and cold in-place recycling, were used. In both technologies reclaimed asphalt pavement (RAP) is bound with bituminous binders (foamed bitumen or bitumen emulsion), hydraulic binders (cement) or a combination of bituminous and hydraulic binders depending on the base course specifications. This paper focuses on the Lithuanian experience in cold recycling of asphalt pavements using different types of cold recycling and binders.
Keywords: bituminous binders; cold in-place recycling; cold in-plant recycling; cold recycling; hydraulic binders; recycling technologies